2011
DOI: 10.1089/ars.2010.3247
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Plasma Membrane Electron Transport in Mammals: Functional Significance in Health and Disease

Abstract: Trans-plasma membrane electron transport (t-PMET) has been established since the 1960s, but it has only been subject to more intensive research in the last decade. The discovery and characterization at the molecular level of its novel components has increased our understanding of how t-PMET regulates distinct cellular functions. This review will give an update on t-PMET, with particular emphasis on how its malfunction relates to some diseases, such as cancer, abnormal cell death, cardiovascular diseases, aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 316 publications
(361 reference statements)
0
36
0
Order By: Relevance
“…However, this is an unusual function for a glycosylphosphatidylinositol-linked protein that is unlikely to utilize reducing equivalents from the cytosol because of linkage to the outer leaflet of the plasma membrane. It is likely that PrP C utilizes extracellular reducing agents for its FR activity such as conversion of ascorbate released from cells to dehydroascorbate through the intermediate ascorbyl free radical [32]. We believe that PrP C itself functions as a ferrireductase based on the following observations: 1) uptake of Fe 3+ is reduced in the liver and kidney of PrP −/− mice, organs involved in storage and reuptake of iron from the glomerular filtrate respectively and likely to express distinct set of proteins on the plasma membrane [this study; 22], and 2) exogenous expression of PrP C on HepG2 cells, proximal kidney tubule epithelial cells [this study; 22], neuroblastoma cells [19], and K562 cells, a hematopoietic cell line [unpublished observations] increases FR activity on the plasma membrane and in cell lysates, indicating a primary role of PrP C in iron uptake.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is an unusual function for a glycosylphosphatidylinositol-linked protein that is unlikely to utilize reducing equivalents from the cytosol because of linkage to the outer leaflet of the plasma membrane. It is likely that PrP C utilizes extracellular reducing agents for its FR activity such as conversion of ascorbate released from cells to dehydroascorbate through the intermediate ascorbyl free radical [32]. We believe that PrP C itself functions as a ferrireductase based on the following observations: 1) uptake of Fe 3+ is reduced in the liver and kidney of PrP −/− mice, organs involved in storage and reuptake of iron from the glomerular filtrate respectively and likely to express distinct set of proteins on the plasma membrane [this study; 22], and 2) exogenous expression of PrP C on HepG2 cells, proximal kidney tubule epithelial cells [this study; 22], neuroblastoma cells [19], and K562 cells, a hematopoietic cell line [unpublished observations] increases FR activity on the plasma membrane and in cell lysates, indicating a primary role of PrP C in iron uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of PALCAR treatment to reduce the appearance of herald I min observed in this study also lead us to propose that changes in the compositions of membrane phospholipid bilayers may alter the biophysical properties of MEP-associated currents in these cells. It also remains to be further investigated whether endogenous PALCAR or lysophosphatidylcholine [15,34] can be a substrate used to enhance MEP-elicited channels which indirectly activate the intrinsic pathway to apoptotic or necrotic changes by inducing changes in the mitochondrial permeability transition pores [2,3,35,36]. …”
Section: Discussionmentioning
confidence: 99%
“…With regard to membrane electron transport, the redox homeostasis of cells is deeply bound to the amount of NAD ? and NADH (Del Principe et al 2011;Gray et al 2011), which ratio is determined by movement of electrons from cellular NADH throughout plasma membrane to an external electron acceptor. In human trials, Herst and Berridge (2006) reported that a trans-membrane changes can act as signaling system capable to regulate the metabolism of host cells and it can change various cell functions such as cell redox homeostasis and protection against diseases.…”
Section: Discussionmentioning
confidence: 99%